2010
DOI: 10.1590/s0006-87052010000100023
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial e temporal do teor de água do solo sob duas formas de uso

Abstract: ); ANTONIO PAZ GONZÁLEZ ( 4 ); GLÉCIO MACHADO SIQUEIRA ( 3, 5 ) RESUMOO objetivo deste trabalho foi analisar a variabilidade espacial do teor de água do solo, ao longo do tempo, em duas condições distintas de uso. Para tanto, foram efetuadas medições do teor de água no solo em área com vegetação natural e outra cultivada com culturas anuais em Galícia, Espanha. O solo foi classificado como Umbrisol (FAO) e as medições foram tomadas em uma parcela plana de 190 m 2 , da qual metade foi mantida com veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
2
7
0
12
Order By: Relevance
“…The variability of soil water availability is a complex study object because storage varies spatially, horizontally and at different depths, mainly due to variations in soil particle size, organic matter content and soil structure, which determine the distribution of pore size, drainage and water retention (Libardi et al, 1986). In addition, the soil management (Vieira et al, 2010), slope and position in the landscape (Rawls & Pachepsky, 2002) affect the spatial variability of soil moisture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of soil water availability is a complex study object because storage varies spatially, horizontally and at different depths, mainly due to variations in soil particle size, organic matter content and soil structure, which determine the distribution of pore size, drainage and water retention (Libardi et al, 1986). In addition, the soil management (Vieira et al, 2010), slope and position in the landscape (Rawls & Pachepsky, 2002) affect the spatial variability of soil moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Vieira et al (2010) studied spatial and temporal variability of moisture in two systems of land use: maize-alfalfa rotation, and bush growth with predominance of pine. They observed that spatial dependence increased during the soil drying cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Conhecer a variabilidade espacial e temporal da disponibilidade hídrica dos solos é de suma importância na quantificação das necessidades hídricas dos vegetais; no entanto, determinações diretas e com a frequência indispensável a este parâmetro são bastante difíceis e trabalhosas em razão do seu comportamento dinâmico, que resulta em grande variabilidade espacial e temporal no solo (Vieira et al, 2010).…”
Section: Introductionunclassified
“…One of the soil physical properties under the influence of organic matter is particle aggregation, which is related to water and air availability to roots and microbes, in addition to mechanical resistance to penetration (Vieira et al, 2010). Besides soil aggregation, organic matter contents play other vital functions in the lifecycle, ranging from microbial and soil fauna activities to positive action on aggregate stability, soil porosity, and soil density, contributing to reduce soil compaction (Spera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%